Envisioning a forest-based circular bioeconomy in sub-Saharan Africa - Center for International Forestry Research (Center for International Forestry Research, 2021)
Climate change and the pandemic have worsened existing inequalities in populations that bear the costs of impacts to which they contributed little. Sustainable, fair and equitable forest-based bioeconomy strategies can build resilience, protect against future epidemics, and contribute to climate mitigation.